ANALISIS KINERJA PEMASARAN UNTUK MENCAPAI KEUNGGULAN BERSAING (Studi Pada Centra Industri Pakaian Batik Di Pekalongan) - Imam Gozali; CH Asta Nugraha (Jurnal Riset Sosial Humaniora dan Pendidikan, 2022)
The goals of the study are to test the effects of strategy orientation, creativation, innovation for marketing perfomance, and the competitive advantages of central batik industry in Pekalongan. The study was done by questionnaire method. Sampling was done by accidental sampling of 100 respondents while techniques were being analyzed using SEM (Structural Equation Model). The result of the study recommends the orientation of strategy, creativity and innovation that influence on the performance of marketing significancy. The orientation of strategy, creativity and innovation affect the competitive advantage through marketing performance too. Marketing performance influence the competitive advantage directly in the apparel industry of central batik in Pekalongan.